Redes sociales y rendimiento académico de las estudiantes de la especialidad de psicología de la Universidad Femenina del Sagrado Corazón (UNIFE) - León Flores, Rey (2015)
The aim of this research is to establish the relationship between social networks and academic performance. The study was done atthe Department of Neurosciences at Universidad Femenina del Sagrado Corazón (UNIFÉ), during the academic semester 2014-I.The study sample corresponded to a non-probabilistic sample of 77 students that often incorporate study using horizontal socialnetworks (Public Networks) and vertical ones (Private Networks). The research was conducted through a quantitative approach andpresented the following characteristics: basic type, correlational level, no experimental design, cross-cutting and expostfáctico. Thesurvey technique was applied by a Questionnaire about the use of social networks, in order to determine such variable and, in thecase of the variable “Academic Performance,” the investigators used the student´s grades. The questionnaire for the variable “socialnetworking” was validated through The Expert Judgment, performed using Cronbach Alpha test. As a result, 0.952 of validity showshigh reliability. As a conclusion, there is a significant relationship between the use of social networks and academic performanceof students of Psychology of the Department of Neuroscience at Universidad Femenina del Sagrado Corazón (UNIFÉ), during theacademic semester 2014-I.